Energy Consumption Management in Buildings in the Context of Voluntary and Mandatory Demand Response Programs in Smart Grids - Khorram Ghahfarrokhi, Mahsa (2021)
Energy consumption is increasing around the world and has been made many consequences such as increasing greenhouse emissions, global warming, and climate changes. Demand response programs can be considered as techniques to manage and control electricity consumption based on user flexibility. There are several types of demand response programs that are categorized in price-based programs and incentive-based programs. This paper analyzes real demand response implementations according to a dataset provided by the Federal Energy Regulatory Commission. Real demand response programs are analyzed based on customer type, program type, potential and capability of the programs, and controllable loads. In the case study, an optimization approach is proposed to control the loads and achieve the power reduction goals of the demand response programs. The obtained results show how buildings can be participants in demand response programs, choosing the more advantageous program.